Your Mess, My Life: The Junction between Land Use Planning and Street Vending in the Accra Mall Enclave - Quarcoo, Joseph Dennis Nii Noi (Department of Environmental and Geographical Science, 2023)
City managers and planners in the global South, particularly in African cities are confronted with an unprecedented urbanisation fraught with complexities such as urban sprawl, jobless growth, and informality. Urban planning practice in Ghana has retained colonial legacies that outlaw informality, be it economic, such as, street trading or housing, such as, slums. This has led to the marginalisation of the urban poor, who make up the majority of urban dwellers. Consequently, the masses invent ways to survive in the city and thus reshape the materiality of urban spaces. Most planners and state officials consider the activities of street vendors as a nuisance that mar the beauty of our cities. For this reason, 24% of the Ghanaian labour force who work on the streets are targets of misaligned and officious controls that include but are not limited to evictions. However, when evicted, most generally return to the streets. Building on existing work on urban planning in the global South and feeding into Southern urban theory, the research focuses explicitly on the Accra Mall Enclave (AME) as a microcosm of African cities. It explores how various players – planners/vendors/politicians – interact and navigate the dynamics of daily experiences. The research asks, how are planners navigating the tensions between planning regulations and the reality of street trading around the Accra Mall Enclave (AME)? What are street traders' logics, strategies, and experiences? How are vendors negotiating their interactions with state actors such as police, planners, city guards, toll collectors, etc.? The questions were answered through qualitative research methods; field observations, interviews, and a review of planning regulations and policies. The results of the study contribute to our understanding of how cities are being built in Africa, particularly Accra, Ghana. As a case study, the focus on the AME assisted in exposing the role of planners in this mode of urbanisation, while also uncovering meaning associated with space and place. Findings show that the state is reluctantly, if not unwillingly, coming to terms with vending within the AME. This could however change quickly if politics change, so still precarious. There are no viable alternatives to relocation, and vendors have established significant relationships and tactics that somehow entrench their position howbeit insecure. Besides all these, state officials, when acting in their individual capacity side with the vending profession because the state has not created jobs. Despite this personal understanding, the system, specifically state bureaucracy, generates obstacles, and as a result existing state structures frustrate the planning practice. This is complicated further by politics. Hence, planners themselves feel helpless, marginalised, and trapped. Further, spatial plans do not adequately provide access to the land needed by informal sector actors. The state resorts to occasional evictions when there is an adequate budget for this action. Imaginations of world class cityness dominate perceptions of the space. This is a candid depiction of the do-nothing scenario – the active contribution of the state in the creation of informality within the AME and the city of Accra, Ghana.